Pengembangan Nilai Moral Peserta Didik dalam Pembelajaran Pendidikan Kewarganegaraan - Amstrongharefa A; Serisman Indah J.Y Zalukhu, Febriana Sri Yuliyanti Putri Gulo, Fiktor Daeli; Wenti Kristiani Harefa, Rejeki Datang, Zoni Zai; Ralex Sander Pratama Lase; Ofonaio Gulo, Ralex Sander Pratama Lase (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Morality is a measure of a person's good and bad, both as individuals and as members of society, and citizens. Meanwhile, moral education is education to make children human beings with good morals and humanity. This paper aims to provide an overview of instilling moral values in students through civic education learning and to understand the definitions of morals, moral education, and moral education in children. The research method used is a literature review research method or library study, which contains theories relevant to the research problems. The conclusion of this paper is that the formation of students' morals is not only from other lessons, but in Civic Education lessons also plays a role in the formation of students' morals